Comparison of radiological and clinical outcome among Kirschner wires versus 3.5 mm diameter cannulated cancellous screw internal fixation in treatment for the displaced lateral humeral condyle fractures in children - Bhati, Lokpal Singh; Gupta, Ashish Kumar; Rathor, Jitendra Singh; Rathore, Devendra Singh; Kundu, Deepak (International Journal of Research in Orthopaedics, 2021)
Background: Lateral humeral condyle fracture, the second most common injury around the elbow, accounts for 10-20% of all fractures of the elbow in children with a high incidence between two and 14 years. Methods: This hospital based prospective randomized comparative study design was include patients of both sexes in age group of 2 to 14 years attending SMS hospital, Jaipur during April 2018 to June 2019 or till the sample size achieved, with due permission from the institutional ethic committee and review board and after taking written informed consent from the patient. Results: 40 patients out of 50 were grouped as excellent (70.1%) while 13 were found good (22.8%) and only four patients were found poor (7.01%) as per Hardacre criteria of assessment of lateral condyle treatment in k wire group while excellent, good and poor results were found 68.4, 24.5 and 7.01% respectively in CC screw groups Conclusions: The displaced fractures (displacement over 2 mm) can be treated successfully by open reduction and K-wires or screw fixation with excellent results.